Characterization of esterases in a Brazilian population of Zaprionus indianus (Diptera : Drosophilidae) - Galego, LGC; Ceron, C. R.; Carareto, CMA (Springer, 2006)
The aim of this study was to characterize esterases in Zaprionus indianus, a drosophilid recently introduced into Brazil. A further aim was study the variation of activity of esterases in the presence of inhibitors and their expression according to sex, sexual activity and age of individual flies. Polymorphisms were detected in two esterase loci (Est-2 and Est-3) and monomorphisms in four others (Est-1, Est-4, Est-5 and Est-6). Biochemical tests using alpha- and beta-naphthyl acetate and the inhibitors malathion, eserine sulphate and PMSF allowed us to classify EST-2 and EST-5 as beta-esterases, both carboxyl-esterases, and EST-1, EST-3, EST-4 and EST-6 as alpha-esterases. EST-1 and EST-3 were classified as carboxyl-esterases and EST-4 and EST-6 as cholinesterases. EST-5 activity was more pronounced in males and EST-2 was restricted to them or to recently copulated females. EST-4, rarely detected, was not characterized. Based on their biochemical characteristics possible roles for these enzymes are suggested.
Keywords: beta-esterases; alpha-esterases; carboxyl-esterases; cholinesterases; Esterases; Zaprionus indianus